Systematic review of outcomes for endoscopic sinus surgery and subsequent aspirin desensitization in aspirin‐exacerbated respiratory disease. Issue 4 (1st December 2020) - Ryan, Lindsey; Segarra, Daniel; Tabor, Mark; Parasher, Arjun
Abstract : Objective: To review and evaluate outcomes of patients with aspirin‐exacerbated respiratory disease (AERD) following endoscopic sinus surgery and subsequent aspirin desensitization. Methods: Electronic searches of OVID MEDLINE (1948 to September 10, 2019), EMBASE (1980 to September 10, 2019), and PubMed were performed on September 10, 2019. A systematic review of the literature was performed using the 2009 PRISMA guidelines. Studies with both preoperative and postoperative data for patients with AERD who underwent sinus surgery and aspirin desensitization were considered appropriate for inclusion. Publications were written in English and included patients aged 18 years or older. Results: Six studies met inclusion criteria for this systematic review. The primary outcome measure was change in symptom profile measured by patient‐reported quality of life scores. The results demonstrate statistically significant improvement in symptoms following endoscopic sinus surgery, with sustained improvement following aspirin desensitization. Revision surgery rates were significantly lower in patients maintained on aspirin therapy. Conclusion: This review suggests that surgery followed by aspirin desensitization results in improvement in both subjective and objective outcome measures. The adjunctive use of aspirin desensitization allows for long‐term stability in symptom scores. Recurrence of polyps and worsening symptoms requiring revision surgery occurs when aspirin maintenance therapy is interrupted.